HIDDEN DISCRIMINATION AND INDIVIDUAL APPROACH IN PEDAGOGICAL PRACTICE - Doncho Donev; Milena Ilieva; Vera Todorova; Veneta Uzunova (Педагогически форум)
The individual approach as a standard way of working with students is one of the most widely-used methods of work in Bulgarian schools. The approach is presented through diverse perspective in the scientific-methodological aspect. However, beyond the level of practical application, quite often the individual approach may be a cover for practices of hidden discrimination on the behalf of teachers toward their students. The article presents the results of a study on hidden discrimination when applying individual approach in Bulgarian schools and kindergartens.